Kajian Estetika Warna Papan Tanda Informasi Pada Restoran Tuttonero di Jakarta Barat - Ratih Pertiwi; irma damayantie (Universitas Bina Sarana Informatika, 2020)
Public space is a container that can accommodate certain activities of the community. This space is a space that is used for transitional activities from the main activities which are usually shaped like a lounge in shops, cafes, and so on. The purpose of the study of the characteristics of information signboards for cafe & restaurant public spaces (case study: West Jakarta) is to provide a description & description through aesthetic studies of the color of information signs found in public spaces of cafes & restaurants located in West Jakarta & its surroundings through color psychology. . The color aesthetic approach is based on the function and influence of color on the emotional atmosphere of visitors. This research method uses qualitative research methods through a phenomenological approach. The phenomenological approach deals with an understanding of how everyday life is, which aims to interpret social action as meaningful and can reconstruct a meaning. The conclusion obtained is based on the phenomenological approach, that the results of this study are the meaning of the white and black colors used on the Tuttonero restaurant information sign board, namely that white reflects light and is considered the color of summer, while the meaning of black is elite, elegant, charming , strong and humble. Therefore, this study recommends further research related to the application of information signboards into public spaces, so that the results will be useful for producers and users of facilities in public spaces of cafes & restaurants.